Introdução à Internet das Coisas Musicais: Prática utilizando Pure Data e Processing - Costa, Rômulo Augusto Vieira; Muchaluat-Saade, Débora; Schiavoni, Flávio (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2022)
The Internet of Musical Things is an interdisciplinary area that draws on principles from computer science and music. It proposes new interactions in art shows, opening new paths for collaborative activities, besides being useful in the teaching these concepts. Despite all these advantages, this area is still unexplored, mainly because it is a novelty and presents several open issues. This work, therefore, aims to exploring the potential of this technology, presenting tools that can be useful in the development of your systems, such as Pure Data and Processing.